Electrochemical Performance and Mechanism of Surface‐Fluorinated Fe3O4 as Stable Anode for Lithium‐Ion Batteries. Issue 4 (9th February 2022) - Mo, Yuyan; Fan, Yajun; Xiao, Xin; Zuo, Xiaoxi; Nan, Junmin
Abstract : Iron oxides are considered as potential anode materials for lithium‐ion batteries thanks to their high theoretical capacity, rich resources, and environmental friendliness. However, the rapid capacity decay and sluggish kinetics greatly limit their practical application. Herein, a simple surface fluorination strategy is developed to greatly improve the electrochemical properties of Fe3 O4 . The fluorinated layer can act as a protective film to stabilize the electrode/electrolyte interface, enhance the wettability of the electrode to shorten the Li + diffusion pathway, and provide more active centers to facilitate charge storage. Consequently, the fabricated fluorinated Fe3 O4 electrode demonstrates high specific capacity (1379 mAh g −1 at 0.5 A g −1 after 300 cycles) and impressive high‐rate performance (876, 802, and 456 mAh g −1 at 5, 10, and 20 A g −1, respectively, after 1000 cycles), which outperforms most of the Fe3 O4 ‐based electrodes recorded so far. This material design strategy may open up a new way for the development of high‐performance anode materials for energy storage based on earth‐rich materials, and advance the understanding of the core role of electrode surfaces/interfaces in battery systems. Abstract : A simple surface fluorination strategy is developed to significantly improve the electrochemical properties of Fe3 O4 anodes. The fluorinated layer stabilizes the electrode/electrolyte interface, shortens the Li + diffusion pathway, and enhances the charge storage capability. Accordingly, the fluorinated electrode has a high specific capacity and impressive high‐rate performance (802/456 mAh g −1 after 1000 cycles at 10/20 A g −1 ).